Consenso informato e DAT. Riprende il cammino parlamentare (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The paper presents the present stage of the parliamentary debate on the law on informed consent and living wills in the Italian Chamber of Deputies.
Keywords: end of life issue; draft law; parliamentary debate; living wills; informed consent